On Medical Standardisation in Times of Scientific Uncertainty: The Management of Flu Epidemics by the French Military Medical Service After the World Pandemic (1920s–30s) - Benoît Pouget (Engaging Science, Technology, and Society)
Using the example of anti-influenza struggle during the 1920s and 1930s, this article asks how the French armed forces health service developed and implemented standardised medical and prophylactic management to face it in times of uncertainty about the nature of the pathogen. The notion of standardisation is placed at the center of the analysis inquiring how exogeneous as endogenous knowledge, norms and practices combined to design the most robust prophylactic and therapeutic strategies possible and their limits. Standardisation is presented as a process of continuous improvement where progressive rationalization of prophylactic measures widely inspired by the Pasteurian school and the improvements in the medical management of influenza patients in a context of therapeutic trial and error required regular changes to standardisation. The article highlights how the proximity between military and civilian actors involved in the production of norms and standards enables us to observe a gradual alignment between medical theories, laboratory research, bedside clinics, preventive measures and treatments used with technical, bureaucratic and organizational systems for the benefit of public health policy.